EMPLOYEE PERFORMANCE REVIEWED FROM LEADERSHIP, MOTIVATION, COMPETENCE AND COMMUNICATION IN TRUCUK SUBDISTRICT KLATEN - Media Ratna; Kartika Hendra Titisari; Istiatin Istiatin (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This research aims to be able to know the influence of leadership, motivation, competence and communication on variables called the performance of employees of Trucuk Subdistrict Klaten. This research has been conducted using an approach called quantitative. The population in this study is all employees in Trucuk Subdistrict Klaten which all numbered 49 people. Sampling techniques use census techniques. Techniques for the analysis of this research data have been used multiple linear regression analysis. The results of the research that has been done show that leadership, motivation, competence and communication have a positive and also significant to the variable called Employee Performance in Trucuk Subdistrict Klaten. It is expected that Trucuk Subdistrict Klaten district in the future will maintain and improve the quality of leadership, motivation, competence and communication of existing employees so that the performance of employees will also continue to improve and certainly become better than before. Keywords: Employee Performance, Leadership, Motivation, Competence and Communication